Influence of Gold Nano-Bipyramid Dimensions on Strong Coupling with Excitons of Monolayer MoS2 - Bradley, Louise (My University, 2020)
Rabi splitting between the longitudinal plasmon of a gold nano-bipyramid and the A exciton of monolayer MoS2 is observed at room temperature. The dependence of the Rabi splitting on the physical dimensions of the nano-bipyramid is reported. The impact of bipyramid length, aspect ratio, and tip radius on the coupling strength is investigated. The mode volume of the nanoresonator is significantly reduced because of the sharp tips of the bipyramid, and the Rabi splitting increases with tip sharpness. The results also reveal that greater Rabi splitting is observed for larger bipyramids, contrasting with results previously reported for different nanoresonator shapes. This shows, for the first time, how the magnitude of the splitting has a different response for particular nanoresonators when tuning the size, without increasing the number of excitons coupled into the system. The Rabi splitting, at zero energy detuning between plasmon and A exciton, increases from ∼55 meV with a 70 nm-long bipyramid to ∼80 meV with a 100 nm-long bipyramid. The increase in coupling strength with size arises because of increasing confinement of the field enhancement at the bipyramid tip.
PUBLISHED
Keywords: Rabi splitting; Plasmon; Exciton; Polariton; Bipyramid; MoS2; Nanoscience & Materials